Multifunctional Gadolinium‐Doped Mesoporous TiO2 Nanobeads: Photoluminescence, Enhanced Spin Relaxation, and Reactive Oxygen Species Photogeneration, Beneficial for Cancer Diagnosis and Treatment. Issue 20 (4th April 2017) - Imani, Roghayeh; Dillert, Ralf; Bahnemann, Detlef W.; Pazoki, Meysam; Apih, Tomaž; Kononenko, Veno; Repar, Neža; Kralj‐Iglič, Veronika; Boschloo, Gerrit; Drobne, Damjana; Edvinsson, Tomas; Iglič, Aleš
Abstract : Materials with controllable multifunctional abilities for optical imaging (OI) and magnetic resonant imaging (MRI) that also can be used in photodynamic therapy are very interesting for future applications. Mesoporous TiO2 sub‐micrometer particles are doped with gadolinium to improve photoluminescence functionality and spin relaxation for MRI, with the added benefit of enhanced generation of reactive oxygen species (ROS). The Gd‐doped TiO2 exhibits red emission at 637 nm that is beneficial for OI and significantly improves MRI relaxation times, with a beneficial decrease in spin–lattice and spin–spin relaxation times. Density functional theory calculations show that Gd 3+ ions introduce impurity energy levels inside the bandgap of anatase TiO2, and also create dipoles that are beneficial for charge separation and decreased electron–hole recombination in the doped lattice. The Gd‐doped TiO2 nanobeads (NBs) show enhanced ability for ROS monitored via OH radical photogeneration, in comparison with undoped TiO2 nanobeads and TiO2 P25, for Gd‐doping up to 10%. Cellular internalization and biocompatibility of TiO2 @ x Gd NBs are tested in vitro on MG‐63 human osteosarcoma cells, showing full biocompatibility. After photoactivation of the particles, anticancer trace by means of ROS photogeneration is observed just after 3 min irradiation. Abstract : Multifunctional TiO2 @ x Gd nanobeads (NBs) show perfect biocompatibility in the absence of light and enhanced reactive oxygen species generation under irradiation, which provides efficient cancer‐cell destruction. Gadolinium doping adds the benefit of optical imaging and significantly improves magnetic resonance imaging relaxation times to the NBs, beneficial for cancer diagnosis.